Meta-Analysis: The Significance Of The Search, Solve, Create, And Share Model In Enhancing Students' Mathematical Problem-Solving Ability - Erina Nurhalisha; Zaenuri Zaenuri; Kristina Wijayanti; Scolastika Mariani; Isnaini Rosyida (Universitas Wiralodra, 2025)
Mathematical problem-solving ability is an important ability that students must have to master mathematics learning and solve problems. The low mathematical problem-solving ability of students is often caused by the application of conventional learning models. One model that can improve students' mathematical problem-solving abilities is the Search, Solve, Create, and Share (SSCS) learning model. The Search, Solve, Create, and Share (SSCS) learning model emphasizes active student participation and problem-solving, significantly enhancing students' mathematical problem-solving abilities. This study was conducted to determine the effectiveness of the SSCS learning model in improving students' capacity for solving mathematical problems. The method employed was meta-analysis. The analysis of eight articles revealed a consistently high effect size across all of them. In addition, the combined effect size of the eight articles was 1.199, which is included in the high category. Based on the results of the t-test, the values ​​of tcount = 30.14 > 1.648 = ttable, so H0 is rejected, indicating that students who engage with the SSCS learning model demonstrate a significantly higher average capability in solving mathematical problems than those who do not use it. Therefore, the SSCS learning paradigm presents a viable alternative for enhancing students' mathematical problem-solving skills.